Synthesis and Study of Structural Properties of Calcium Oxide Nanoparticles Produced by Laser-Induced Plasma and its Effect on Antibacterial Activity - Ibrahim Karim Abbas; Kadhim Abdulwahid Aadim (Science and Technology Indonesia, 2022)
A LIBS technique was used to investigate the antibacterial activity of calcium oxide nanoparticles (CaO NPs). CaO NPs were prepared using a Q-switched Nd: YAG pulsed laser with a fundamental wavelength of 1064 nm at different energies (400-600 mJ) and constant frequency (6 Hz). A calcium powder sample was prepared after being pressed into a disc with a diameter of 1 cm. Analyzing X-ray diffraction (XRD) showed the crystalline structure of CaO NPs, crystalline size was 30.99±2 and 34.20±2.2 nm for laser energy 500 and 600 mJ. (FE-SEM) to reveal the topography of produced CaO NPs, the results showed a homogenous compact and dense surface with the formation of CaO NPs like flakes, cubes, and tubes. Atomic force microscopy (AFM) has shown that the CaO NPs were nanoscale and had a coordinated surface structures. The results also revealed the stabilizing zeta potential of the prepared CaO NPs, average (ZP) -18.3±1.6 mV in 600 mJ and -8.8±2.3 mV for 500 mJ. Different laser energies used in preparing CaO NPs resulted in the varying killing of the number of bacteria Klebsiella pneumoniae and Staphylococcus aureus bacteria. Complete bacterial inhibition or cell growth inactivation was found when the laser energy prepared for the CaO NPs was 600 mJ.